Вариации на тему идентичности для социокультурного оркестра - Черныш, Н.; Ровенчак, О. (Социология: теория, методы, маркетинг, 2007)
The article concretizes an application of sociocultural approach to the identity studies in sociology. It analyzes the works of Ukrainian and foreign researchers concerning the identity studies within this approach. The authors emphasize contemporary reidentification processes and gaining the newest identities under global transformations.